Copper-based catalyst protected by oxide layer as well as preparation method and application of copper-based catalyst

By introducing transition metal oxide nanoclusters protected by oxide layer into copper-based catalysts, the problem of insufficient selectivity and stability of copper-based catalysts in CO2 electroreduction reaction is solved, and efficient conversion of multi-carbon products and long-term stability is achieved. .

CN119506957AActive Publication Date: 2025-02-25ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411643634.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing copper-based catalysts have problems such as selectivity, low multi-carbon product generation efficiency and insufficient catalyst stability in CO2 electroreduction reaction.

Method used

The copper-based catalyst structure MOx-Cu2O/Cu is protected by the oxide layer. By introducing transition metal oxide nanoclusters (MOy) with oxygen defects, it can achieve efficient conversion of CO2 into multi-carbon products and improve the catalyst. structural stability.

Benefits of technology

The Faraday efficiency of the multi-carbon product is significantly improved to reach more than 80%, and the catalyst shows good stability under reaction conditions, extending the life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506957A_ABST
    Figure CN119506957A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-based catalyst protected by an oxide layer as well as a preparation method and application of the copper-based catalyst. The structure of the copper-based catalyst represents MOy-Cu2O / Cu, MOy is a transition metal oxide nanocluster containing oxygen vacancies, Cu is a copper nanoparticle substrate, MOy is dispersed on the Cu substrate in a coating manner, and Cu2O is distributed at a heterogeneous interface of MOy and Cu nanoparticles; and MOy is an oxide of any one of transition metals of Zn, Ga, Zr and In with oxygen defects. MOy clusters are dispersed on a heterogeneous Cu-Cu < + > substrate, Cu sites in different coordination states form a heterostructure by adopting an atmosphere induction method, the problem of CO2 activation is effectively solved, the generation efficiency of a CO2 electroreduction reaction is enhanced through the synergistic effect of Cu and Cu < + > sites, proton-electron coupling transfer kinetics is accelerated, C-C coupling is promoted, and the CO2 electroreduction reaction efficiency is improved. The high current density can be achieved under the low overpotential, and the Faraday efficiency of the generated multi-carbon product can reach 80% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon resource recycling, and in particular to an oxide layer-protected copper-based catalyst and a preparation method and application thereof. Background Art

[0002] With the intensification of global climate change and energy crisis, reducing carbon dioxide (CO2) emissions and developing renewable energy have become important directions of current scientific research. CO2 electroreduction reaction (CO2RR) is a method of converting CO2 into valuable chemicals or fuels by electrochemical means, which has the potential to reduce CO2 emissions and achieve carbon resource recycling. However, existing catalysts still face many challenges in terms of selectivity, efficiency of multi-carbon product generation and stability.

[0003] Copper-based catalysts have attracted much attention due to their excellent performance in generating multi-carbon products, mainly because copper sites can effectively promote CC coupling reactions to generate multi-carbon products. However, traditional copper catalysts are prone to morphological changes during the reaction, resulting in decreased catalytic performance. In addition, intermediates such as carbonates are easily formed on the copper surface, hindering the reaction.

[0004] Oxidation state is defined as “the degree of oxidation of an atom based on electron counts”. Determining the oxidation state can reveal the chemical state of an element and rationalize the design of electrocatalysts. By adjusting the oxidation state, the number of valence electrons can be changed, thereby changing the electron distribution. For transition metal atoms, adjusting the oxidation state can change the arrangement of empty d orbitals and unpaired d electrons, which is crucial for electron transfer to reactants.

[0005] In recent years, researchers have found that (Nat Catal 2, 709–717 (2019) Nat Commun 15, 7820 (2024)) the introduction of monovalent copper (Cu + ) sites can significantly improve the catalytic performance. + The unique electronic structure of the site facilitates the adsorption and activation of intermediates, thus promoting CC coupling. + The composite active sites can work synergistically, Cu + The Cu site facilitates the coupling of CO intermediates, while the Cu site facilitates further hydrogenation reactions, thereby improving the selectivity and generation efficiency of multi-carbon products.

[0006] CN 111821985 A discloses a copper-based catalyst with a specific surface area of ​​200-350 square meters / gram and an average pore size of 5-15 nanometers, and at least a copper-containing mixture and a carrier. In the copper-containing mixture, the valence of copper is positive monovalent and positive divalent, and the carrier composed of at least silicon oxide, zirconium oxide, yttrium oxide, germanium oxide, magnesium oxide and graphite fiber is combined to provide suitable surface acidity and alkalinity to increase the interaction between the copper species in the copper-containing mixture and the carrier, which is beneficial to the high dispersion of the copper-containing mixture in the carrier, so as to improve the raw material conversion rate and product selectivity in the dimethyl oxalate hydrogenation reaction process, and on the other hand, it is also beneficial to improve the service life of the copper-based catalyst, so as to facilitate large-scale industrial production.

[0007] CN112899709A discloses a copper-based compound / copper nano-electrode with interfacial synergistic effect, and its preparation method and application. The electrode comprises a conductive substrate and a copper-based compound / copper nano-catalyst loaded on the surface; the copper-based compound includes, but is not limited to, cuprous oxide, copper nitride, copper oxide and other compounds. The electrode material with interfacial regulation function utilizes the synergistic effect of monovalent copper / zero-valent copper, divalent copper / zero-valent copper and divalent copper / monovalent copper / zero-valent copper to reduce the reaction energy barrier of carbon monoxide dimerization, thereby effectively inhibiting the hydrogen evolution reaction during electrochemical carbon dioxide reduction, and having good selectivity for multi-carbon products ethylene, ethanol and isopropanol.

[0008] However, the preparation methods of the catalysts in the above technologies are complicated and require precise control of conditions such as temperature, time, pH value and concentration, which increases the cost; and the Faraday efficiency of multi-carbon products may still have room for improvement. + The kinetic behavior of the sites during the electroreduction process is complex and they are easily reduced, resulting in a decrease in reaction performance; therefore, catalysts with higher selectivity for multi-carbon products, higher catalytic efficiency, and greater stability will have broad application prospects. Summary of the invention

[0009] The present invention aims to solve the problems of low selectivity, low efficiency in producing multi-carbon products and insufficient catalyst stability of copper-based catalysts in CO2RR, and provides a copper-based catalyst protected by an oxide layer, introduces a transition metal oxide to protect the heterogeneous interface, realizes efficient conversion of CO2 into multi-carbon products, and improves the stability of the catalyst structure.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] A copper-based catalyst protected by an oxide layer, wherein the copper-based catalyst structure represents MO x -Cu2O / Cu,MO yis a transition metal oxide nanocluster containing oxygen defects, Cu is a copper nanoparticle substrate, and MO x Coating dispersed on the Cu substrate, Cu2O distributed in MO y and Cu nanoparticles at the heterointerface;

[0012] The MO y It is an oxide of any transition metal among Zn, Ga, Zr and In with oxygen defects; the copper element in the copper-based catalyst accounts for more than 50wt% of the total molar amount of metal elements.

[0013] Considering that the Cu site with different coordination environments is still the main active site for CC coupling, the catalyst structure is designed as MO y -Cu2O / Cu(inverse structure), MO y Clusters dispersed in heterogeneous Cu-Cu + On this basis, the construction of the reverse Cu-oxide interface may further adjust the adsorption energy of specific intermediates by providing new degrees of freedom, thereby adjusting the product distribution. Metal oxides with abundant Lewis acid sites can promote the activation of CO2 molecules, and the Cu-oxide interface boundary exhibits different CO* adsorption strengths and reaction energy barriers for CC coupling, thereby improving the selectivity for specific multi-carbon products. The protection of the oxide layer can also further stabilize the Cu + The catalyst not only exhibits excellent catalytic performance under laboratory conditions, but also has good stability, showing broad application prospects.

[0014] The copper element Cu in the copper-based catalyst 0 The molar content is 10%-80%, Cu + The molar content is 10%-80%. The oxide is highly dispersed on Cu as a small component; when the Cu content is low, it will be difficult for the oxide to achieve high dispersion and the interface abundance will also decrease. However, the more the better. Preferably, Cu + The molar content is 5-50%.

[0015] The particle size of the copper nanoparticles in the copper-based catalyst is below 100 nm. y The particle size of nanoparticles is below 50nm.

[0016] The present invention also provides a method for preparing the copper-based catalyst protected by the oxide layer, comprising the steps of:

[0017] Step 1: Mix copper nanoparticles and transition metal complexes, calcine, and then reduce them with hydrogen to obtain MO y / Cu powder;

[0018] Step 2: MO y / Cu powder is induced to react in an alcohol vapor environment to obtain the copper-based catalyst MO x -Cu2O / Cu.

[0019] In the present invention, copper nanoparticles and transition metal ligands are mixed, calcined once, reduced with hydrogen, and then induced with alcohol vapor atmosphere to obtain a reverse phase catalyst. The preparation method is simple, green and has mild conditions.

[0020] The copper nanoparticles can be made by yourself or purchased. The process of making the copper nanoparticles by yourself includes: fully mixing the copper precursor and the dispersant in a solvent, slowly adding a reducing agent to react, washing, and drying to obtain the copper nanoparticles;

[0021] The copper precursor is an organic or inorganic salt of copper; preferably, the copper precursor includes one or more of copper acetate, copper nitrate, copper oxalate, copper halide or copper carbonate;

[0022] The dispersant includes common organic and inorganic dispersants, such as one or more of ethanol, methanol, and water; the reducing agent includes one or more of ascorbic acid, sodium borohydride, or potassium borohydride; and a stabilizer may also be added during the reaction, such as one or more of polyethylene glycol, sodium citrate, and polyvinyl pyrrolidone.

[0023] The transition metal ligand includes one or more of bis(2,2'-bipyridine)bis(oxalate)zinc(II), bis(2,2'-bipyridine)bis(acetate)zinc(II), bis(bipyridine)bis(acetate)gallium(III), bis(bipyridine)bis(oxalate)gallium(III), bis(bipyridine)bis(citrate)zirconium(IV) or bis(bipyridine)bis(oxalate)zirconium(IV).

[0024] The transition metal ligand can be purchased or made by oneself. The making process includes fully mixing the transition metal precursor and the dispersant at room temperature, fully mixing the required multidentate ligand and the dispersant, and then slowly adding them to the precursor solution. After sufficient reaction, washing, drying and calcining are performed.

[0025] The transition metal precursor includes oxides, organic salts or inorganic salts of transition metals; such as zinc oxide, zinc acetate, zinc nitrate, zinc carbonate, zinc chloride, gallium oxide, gallium nitrate, gallium carbonate, gallium acetate, gallium chloride, zirconium oxide, zirconium acetate, zirconium nitrate, zirconium chloride, indium oxide, indium nitrate, indium chloride, etc.;

[0026] The dispersant includes common organic and inorganic dispersants, such as one or more of ethanol, methanol, and water;

[0027] The multidentate ligand includes a compound containing any one of the structures of bipyridine, oxalate, acetate, citrate, etc.;

[0028] The particle sizes of the copper nanoparticles and transition metal coordination particles are both below 2 microns;

[0029] When the copper nanoparticles and the transition metal coordination particles are mixed in step 1, the molar ratio of the copper element to the transition metal element is 2:1 to 10:1, preferably, the molar ratio of the copper element to the transition metal element is 5:1 to 10:1;

[0030] The mixing includes one or more combinations of mechanical mixing, impregnation or co-precipitation. The mixing promotes the full dispersion of the two elements and creates oxygen vacancies at the interface between the two phases, which is more conducive to subsequent reactions.

[0031] Preferably, the mixing is carried out by ball milling for 1-6 hours, which is more conducive to the production of oxygen vacancies.

[0032] The calcination temperature is 100-400°C and the calcination time is 1-20 hours. It ensures that organic and inorganic impurities are removed and Cu interacts with transition metal oxides. Preferably, the calcination temperature is 200-400°C and the calcination time is 2-6 hours;

[0033] The reaction temperature of the hydrogen reduction is 100-400°C, and the reaction time is 1-20h. Preferably, the hydrogen reduction reaction is carried out at 200-400°C, and the reduction time is 1-3h;

[0034] The alcohol vapor includes methanol, ethanol, n-propanol, isopropanol, n-butanol, or a mixture of two or more thereof; preferably, the alcohol vapor is ethanol vapor.

[0035] The induction reaction temperature is 100-400°C, and the reaction time is 1-20h. Ensure that it fully interacts with the continuous Cu surface. If the temperature is too low, it cannot fully gasify and react with Cu, and if the reduction temperature is too high, the material structure will be destroyed. Preferably, the induction reaction is at 200-400°C, and the reaction time is 1-4h.

[0036] The present invention also provides the use of the copper-based catalyst protected by the oxide layer in a carbon dioxide reduction reaction.

[0037] The catalyst obtained by the present invention can be coated on a large surface conductive material, including but not limited to one or a combination of two or more of carbon paper, carbon cloth, glassy carbon electrode, etc. The reaction potential is -0.6V to -2.5V (relative to mercury / mercuric oxide reference electrode) at room temperature and pressure, and the electrocatalytic conditions of the electrolyte including but not limited to KOH, KHCO3, NaOH, NaHCO3 and other commonly used electrolytes can promote the reduction of carbon dioxide to carbon monoxide, formic acid, ethylene, ethanol, acetic acid and other products.

[0038] Under the electrocatalysis of the copper-based catalyst, the Faraday efficiency of the multi-carbon product is above 50%; the multi-carbon product includes one or more of acetic acid, ethylene, ethanol, and isopropanol.

[0039] Preferably, the total Faraday efficiency of the multi-carbon product is above 80%; in particular, at a current density of 300 mA cm -2 Above, the Faraday efficiency of ethanol can reach more than 70%.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The present invention adopts the method of atmosphere induction to form a heterogeneous structure of Cu sites with different coordination states, which effectively solves the activation problem of CO2. + The synergistic effect of the sites enhances the generation efficiency of the CO2 electroreduction reaction, accelerates the proton-electron coupling transfer kinetics, promotes CC coupling, and can achieve higher current density at lower overpotentials. The Faradaic efficiency of generating multi-carbon products can reach more than 80%.

[0042] (2) The introduced oxide protective layer effectively stabilizes Cu under electroreduction conditions + Species, so that the catalyst prepared by the present invention shows good stability under reaction conditions, can maintain high activity for a long time without obvious performance decay. The catalyst preparation process is simple, easy to operate, and the raw materials are simple and easy to obtain, with industrial application potential, suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Preparation of copper-based catalyst ZnO protected by oxide layer for Example 1 1-x -X-ray diffraction spectrum of Cu2O / Cu.

[0044] Figure 2 Preparation of copper-based catalyst ZnO protected by oxide layer for Example 1 1-x -TEM image (a) and EDX mapping image (b) of the X-ray diffraction spectrum of Cu2O / Cu.

[0045] Figure 3 Preparation of copper-based catalyst ZnO protected by oxide layer for Example 1 1-x -XPS pattern of Cu2O / Cu.

[0046] Figure 4 This is a performance diagram of the copper-based catalyst protected by an oxide layer prepared in the embodiment of the application example for catalyzing the electroreduction of CO2 to produce multi-carbon products.

[0047] Figure 5 This is a stability test chart of the copper-based catalyst protected by an oxide layer prepared in the embodiment of the application example to catalyze the electro-reduction of CO2 to produce multi-carbon products.

[0048] Figure 6 This is a performance comparison chart of the copper-based catalyst protected by an oxide layer prepared in the embodiment and comparative example in the application example for catalyzing the electroreduction of CO2 to produce multi-carbon products. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0050] The raw materials used in the following specific embodiments are all purchased from the market. The transition metal oxide containing oxygen defects is expressed as the corresponding atomic number -x according to the number of O atoms, where x refers to the amount of oxygen defects, such as MO y When it is zinc oxide, it is represented by ZnO 1-x ; When it is gallium oxide, it is expressed as Ga2O 3-x .

[0051] Example 1 Oxide layer protected copper-based ZnO 1-x -Cu2O / Cu catalyst

[0052] (1) 500 mg of anhydrous copper acetate and 2 g of PVP polyvinyl pyrrolidone were dispersed in 50 mL of ethanol under a constant temperature of 60°C in a water bath. 1600 mg of ascorbic acid was prepared into 80 mL of solution and gradually added dropwise to the above solution, and continued to stir in a constant temperature of 60°C in a water bath for 1 hour. The obtained orange-red solution was centrifuged and dried in an oven overnight to obtain a Cu nanoparticle solid powder with a particle size of 50 nm;

[0053] (2) Ultrasonic dispersion of 476 mg of Zn(NO3)2·6H2O in 20 mL of deionized water; ultrasonic dispersion of 250 mg of 2,2'-bipyridine in 10 mL of methanol; and ultrasonic dispersion of 101 mg of oxalic acid in 10 mL of deionized water; then, the latter two solutions were added to the zinc nitrate solution under stirring conditions, and continued to stir at room temperature for 1 hour. The obtained white solution was centrifuged and dried in an oven overnight. The obtained solid powder was recorded as di(bipyridine)di(oxalate)zinc(II)ZnBO, with a particle size of 20 nm;

[0054] (3) The solid powder was added into a ball mill according to a Cu:Zn molar ratio of 8:2, and a certain amount of ZrO2 grinding balls were added thereto, and the ball-to-material ratio was 15:1. A planetary ball mill was used for grinding at a speed of 870 rpm for 4 h, and the obtained solid was taken out and calcined in a muffle furnace at 400°C for 4 h.

[0055] (4) The calcined solid powder was taken out and reduced at 300°C in a H2 atmosphere for 1 h to obtain ZnO 1-x / Cu powder, and then ethanol vapor at a flow rate of 30 ml / min was introduced into it, and induced at 300 ° C for 1 h to obtain a catalyst with a heterogeneous interface of copper and cuprous oxide, which was recorded as ZnO 1-x -Cu2O / Cu.

[0056] Figure 1 Copper-based catalyst ZnO protected by oxide layer 1-x -X-ray diffraction spectrum of Cu2O / Cu. Figure 1 It can be seen that there is Cu on the catalyst 0 and Cu + crystalline structure.

[0057] Figure 2 Copper-based catalyst ZnO protected by oxide layer 1-x -TEM image (a) and EDX mapping image (b) of the X-ray diffraction spectrum of Cu2O / Cu. Figure 2 It can be seen that ZnO 1-x The particles are evenly distributed on Cu with a size of 1-5nm, the size of Cu is 10-30nm, and the size of Cu is 1-20nm. + Distributed in Cu-ZnO 1-x At the interface.

[0058] Figure 3 Copper-based catalyst ZnO protected by oxide layer 1-x -XPS graph of Cu2O / Cu. Figure 3 It can be seen that the prepared catalyst is rich in Cu 0 and Cu + Species.

[0059] Example 2-3

[0060] According to the preparation process of Example 1, the type of alcohol vapor in step 4 was changed to methanol and n-propanol to obtain copper-based catalysts protected by an oxide layer, which were respectively denoted as M-ZnO 1-x -Cu2O / Cu, P-ZnO 1-x -Cu2O / Cu.

[0061] Embodiment 4-6

[0062] According to the preparation process of Example 1, the time of the ethanol atmosphere-induced reduction reaction in step 4 was changed to 0.5 h, 2 h, and 4 h to obtain a copper-based catalyst protected by an oxide layer.

[0063] Example 7

[0064] (1) 500 mg of anhydrous copper acetate and 2 g of PVP polyvinyl pyrrolidone were dispersed in 50 mL of ethanol under a constant temperature of 60°C in a water bath. 1600 mg of ascorbic acid was prepared into 80 mL of solution and gradually added dropwise to the above solution, and continued to stir in a constant temperature of 60°C in a water bath for 1 hour. The obtained orange-red solution was centrifuged and dried in an oven overnight to obtain a Cu nanoparticle solid powder with a particle size of 50 nm;

[0065] (2) Ultrasonic dispersion of 282 mg of GaCl3 in 20 mL of deionized water; ultrasonic dispersion of 250 mg of 2,2'-bipyridine in 10 mL of methanol; ultrasonic dispersion of 101 mg of oxalic acid in 10 mL of deionized water; then, the latter two solutions were added to the gallium chloride solution under stirring conditions, and continued to stir at room temperature for 1 hour. The obtained white solution was centrifuged and dried in an oven overnight to obtain a solid powder of di(bipyridine)di(oxalate)gallium(III);

[0066] (3) The solid powder was added into a ball mill according to a Cu:Zn molar ratio of 8:2, and a certain amount of ZrO2 grinding balls were added thereto, and the ball-to-material ratio was 15:1. A planetary ball mill was used for grinding at a speed of 870 rpm for 4 h, and the obtained solid was taken out and calcined in a muffle furnace at 400°C for 4 h.

[0067] (4) The calcined solid powder was taken out and reduced at 300°C in a H2 atmosphere for 1 h to obtain Ga2O 3-x / Cu powder, and then ethanol vapor was introduced into it and induced at 300℃ for 1h to obtain a copper and cuprous oxide heterogeneous interface catalyst protected by gallium oxide, which was recorded as Ga2O 3-x -Cu2O / Cu.

[0068] Comparative Example 1

[0069] According to the preparation process of Example 1, without the alcohol atmosphere induction step, ZnO is directly obtained in step 4. 1-x / Cu powder.

[0070] Comparative Example 2

[0071] According to the preparation process of Example 1, the Cu nanoparticles added in step 3 were replaced with Cu2O nanopowder with a particle size of about 50 nm to obtain the corresponding catalyst ZnO 1-x / Cu2O.

[0072] Comparative Example 3

[0073] According to the preparation process of Example 1, the solid powder added in step 3 is added to the ball mill according to the molar ratio of Cu:Zn replaced with 4:6, and the subsequent steps are consistent with Example 1 to obtain the corresponding catalyst.

[0074] Application Examples

[0075] The catalysts prepared in Examples 1-7 and Comparative Examples 1-3 were evaluated for their electrocatalytic CO2 reduction performance. The catalysts were coated on the surface of a gas diffusion electrode to form a working electrode, an iridium-plated titanium plate was used as a counter electrode, and a Hg / HgO electrode was used as a reference electrode. The reaction was carried out in a flow electrolytic cell.

[0076] Reaction conditions: The working electrode was prepared by dispersing 10 mg of the catalyst in 670 μL of water and 30 μL of Nafion solution (5 wt%), followed by 30 min of ultrasonic treatment to obtain a uniform slurry. This mixture was dripped onto the gas diffusion layer to achieve 1 mg cm -2 The catalyst loading was 10 mL min using a peristaltic pump. -1 Before the test, high-purity CO2 was circulated at a flow rate of 15 mL min -1 The reaction time was controlled at each potential, and the related products were quantitatively analyzed by gas chromatography and nuclear magnetic resonance. The carbon-one products mainly included CO and HCOOH, and the multi-carbon products mainly included C2H5OH, C2H4 and CH3COOH.

[0077] Figure 4 This is a performance diagram of the copper-based catalyst protected by an oxide layer prepared in Example 1 for catalyzing the electroreduction of CO2 to produce multi-carbon products. Figure 4 It can be seen that the catalyst exhibits excellent performance throughout the entire operating range, reaching the optimum at 0.9 V vs. RHE.

[0078] Figure 5 This is a stability test diagram of preparing multi-carbon products by electro-reduction of CO2 catalyzed by copper-based catalysts protected by an oxide layer in Example 1. The stability test was conducted in a flow cell using the same electrolyte and gas-liquid flow rate as in the conventional test, with -0.9 V vs. RHE selected as the fixed reaction potential, and the liquid phase products were analyzed every 1-3 hours. Figure 5 It can be seen that after running for more than 200 h, the performance of the catalyst did not decrease significantly, showing good stability.

[0079] The carbon one product and multi-carbon product Faraday efficiencies of the catalysts of the embodiments and comparative examples are shown in Tables 1 and Figure 6As shown, it can be seen that Examples 1-6 all formed a heterogeneous interface between copper and cuprous oxide, and at the same time formed an inverse loading with the transition metal oxide. The selectivity and efficiency of CO2 electroreduction to generate multi-carbon products were improved through the synergistic effect of Cu and Cu sites and the interface structure and optimization.

[0080] The comparison between Examples 1-3 shows that different atmospheres induce + The influence of ethanol vapor is different under the same conditions. + Both the number and dispersion of species are more conducive to multi-step proton-electron coupling transfer and the corresponding CC coupling.

[0081] The comparison between Examples 1, 4, 5, and 6 shows that the effect of the duration of ethanol atmosphere induction is not that the longer the treatment time, the better. In fact, as the treatment time increases, the relative advantage of the dominant product in the multi-carbon product decreases after the initial increase. In Example 7, the change of the transition metal oxide has an impact on the overall structure of the catalyst, especially Cu + The dynamic changes of species in the reaction process have an important influence, Cu + The higher the content of the species, the better. It can be inferred that there are certain differences in the adsorption capacity and ability to induce electron transfer of ethanol at different interfaces.

[0082] Comparative Examples 1 and 2 failed to successfully form a heterogeneous interface between copper and cuprous oxide, indicating that the promotion effect of the Cu site in a single coordination environment on CC coupling is limited.

[0083] In Comparative Example 3, due to the low content of Cu, oxide became the main component, and high dispersion was not achieved. The interface abundance was also relatively low. Only less than 6% Cu was generated after alcohol treatment. + species, and due to the increase in the proportion of oxides, the conductivity decreases significantly and the overall performance is poor.

[0084] Comparative Example 4: Since the co-precipitation method was used for loading, the binding strength of the two components was relatively weak, the interface abundance, especially the defect abundance at the interface, was low, and the Cu was not induced after alcohol treatment. + species, and due to poor oxide dispersion, the overall performance is also poor.

[0085] Table 1 Faraday efficiency of carbon one product and multi-carbon product of catalysts of Examples and Comparative Examples

[0086]

Claims

1. A copper-based catalyst protected by an oxide layer, characterized in that: The copper-based catalyst structure represents MO y -Cu2O / Cu,MO y is a transition metal oxide nanocluster containing oxygen defects, Cu is a copper nanoparticle substrate, and MO y Coating dispersed on the Cu substrate, Cu2O distributed in MO y and Cu nanoparticles at the heterointerface; The MO y It is an oxide of any transition metal among Zn, Ga, Zr and In with oxygen defects; the copper element in the copper-based catalyst accounts for more than 50wt% of the total molar amount of metal elements.

2. The copper-based catalyst protected by an oxide layer according to claim 1, characterized in that: The copper element Cu in the copper-based catalyst 0 The molar content is 10%-80%, Cu + The molar content is 10%-80%.

3. The copper-based catalyst protected by an oxide layer according to claim 1, characterized in that: The particle size of the copper nanoparticles in the copper-based catalyst is below 100 nm. y The particle size of nanoparticles is below 50nm.

4. The method for preparing an oxide layer-protected copper-based catalyst according to any one of claims 1 to 3, characterized in that: Includes steps: Step 1: Mix copper nanoparticles and transition metal complexes, calcine, and then reduce them with hydrogen to obtain MO y / Cu powder; Step 2: MO y / Cu powder is induced to react in an alcohol vapor environment to obtain the copper-based catalyst MO y -Cu2O / Cu.

5. The method for preparing an oxide layer-protected copper-based catalyst according to claim 4, characterized in that: When the copper nanoparticles and the transition metal coordination particles are mixed in step 1, the molar ratio of the copper element to the transition metal element is 2:1 to 10:1; The transition metal ligand includes one or more of bis(2,2'-bipyridine)bis(oxalate)zinc(II), bis(2,2'-bipyridine)bis(acetate)zinc(II), bis(bipyridine)bis(acetate)gallium(III), bis(bipyridine)bis(oxalate)gallium(III), bis(bipyridine)bis(citrate)zirconium(IV) or bis(bipyridine)bis(oxalate)zirconium(IV).

6. The method for preparing the copper-based catalyst protected by an oxide layer according to claim 4, characterized in that: The particle sizes of the copper nanoparticles and transition metal coordination particles are both below 2 microns; The mixing includes one or more combinations of mechanical mixing, impregnation or co-precipitation.

7. The method for preparing an oxide layer-protected copper-based catalyst according to claim 4, characterized in that: The calcination temperature is 100-400°C and the calcination time is 1-20h; The reaction temperature of the hydrogen reduction is 100-400° C., and the reaction time is 1-20 hours.

8. The method for preparing an oxide layer-protected copper-based catalyst according to claim 4, characterized in that: The alcohol vapor includes one or a mixed vapor of two or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol; The induction reaction temperature is 100-400° C., and the reaction time is 1-20 hours.

9. Use of the copper-based catalyst protected by an oxide layer according to any one of claims 1 to 3 in a carbon dioxide reduction reaction.

10. The use of the copper-based catalyst protected by an oxide layer according to claim 9 in a carbon dioxide reduction reaction, characterized in that: Under the electrocatalysis of the copper-based catalyst, the Faraday efficiency of the multi-carbon product is above 50%; the multi-carbon product includes one or more of acetic acid, ethylene, ethanol, and isopropanol.

Citation Information

Patent Citations

  • Preparation method of CuO / Cu2O / Cu ternary composite material

    CN110152665A

  • Preparation method of activated carbon loaded ZnO / CuO or ZnO / CuO / Cu2O photocatalytic composite powder

    CN111036189A

  • Preparation method and application of bifunctional series copper-based electro-catalysis nano material

    CN115896816A

  • Monatomic alloying catalyst for synthesizing CO through electrocatalysis of CO2 and preparation method of monatomic alloying catalyst

    CN117026283A

  • Reverse catalyst rich in surface oxygen vacancy defect as well as preparation method and application of reverse catalyst

    CN118217990A